2008
DOI: 10.4081/jlimnol.2008.128
|View full text |Cite
|
Sign up to set email alerts
|

The role of cell-surface-bound phosphatases in species competition within natural phytoplankton assemblage: an in situ experiment

Abstract: Despite it is widely acknowledged that the ability to hydrolyze dissolved organic matter using extracellular phosphatases is diverse in freshwater phytoplankton, the competition within single species related to presence and quantity of cell-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…The standard protocol initially appeared to be showing differential labeling in the diatom epiphytes versus Cladophora filaments. While cell age may influence APA (Štrojsová et al. 2008), incubation conditions were observed to be important to labeling success; clear APA labeling was also shown in Cladophora when ethanol fixation was omitted.…”
mentioning
confidence: 99%
“…The standard protocol initially appeared to be showing differential labeling in the diatom epiphytes versus Cladophora filaments. While cell age may influence APA (Štrojsová et al. 2008), incubation conditions were observed to be important to labeling success; clear APA labeling was also shown in Cladophora when ethanol fixation was omitted.…”
mentioning
confidence: 99%
“…Table 3). Studies applying the FLEA technique have revealed that, in most natural environments, only a part of a particular population was labelled (Š trojsová et al 2003, 2005, 2008Dignum et al 2004;Cao et al 2005;Dyhrman and Ruttenberg 2006;Ou et al 2006; this study), which might indicate that physiological need for P is diverse also at the population level.…”
Section: Resultsmentioning
confidence: 72%
“…Rengefors et al. (2003) and Štrojsová et al. (2008) explained similar results by different P demand of particular species, various internal P supply, or distinct physiological conditions of species (cf.…”
Section: Discussionmentioning
confidence: 74%
“…Application of the FLEA assay indicated differences in the presence and localization of phosphatases among the phytoplankton and both short‐term and seasonal variations of PA (Rengefors et al. 2001, 2003, Štrojsová et al. 2003, 2005, 2008, Dignum et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation